PENGARUH METODE BERMAIN PERAN TERHADAP KETERAMPILAN BERCERITA MATA PELAJARAN BAHASA INDONESIA KELAS II MI TARBIYATUS SYIBYAN - Eka Ramiati; Nina Nurazizah (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2023)
This research was motivated by difficulties in storytelling skills in Indonesian subjects. So that students have difficulty in expressing ideas, and ideas when teachers ask students to tell stories, students tend to be lazy if the subject Indonesian.Learning storytelling skills in Indonesian subjects through this role-playing method is a game that is used as a place to act out characters, objects, plants or animals around them, so as to make students tell stories by paying attention to (1) the choice of words and sentences, (2) fluency and accuracy, and (3) the expressions shown. This study aims to determine whether or not there is an influence of the use of role-playing methods on the storytelling skills of Indonesian subjects. The type of research used is pre-experimental quantitative research with one group pretes-postes design. The data collection method used is a test performance to determine the storytelling skills of Indonesian subjects using role-playing methods. The subjects of this study were 25 students who were taken through purposive sampling data collection techniques. The data analysis technique used is the t-test or t-test. Based on the results of the calculation, the data obtained is significant at 0.000 smaller than 0.05. Which means a signification of 0.000<0.05. Thus, this shows that the influence of role-playing methods on the storytelling skills of Indonesian subjects is acceptable. It means Ha is accepted and Ho is rejected